Collaborative Governance, Sejauh Mana Mampu Menyelesaikan Konflik? (Studi Pada Desa Pakel, Kabupaten Banyuwangi) - Leni Oktopiani; Idil Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Pakel Village is one of the villages in Banyuwangi Regency with prolonged agrarian conflict. The agrarian conflict occurred due to the management of plantation land concerning the former Dutch colony plantation between the community and PT Bumi Sari Maju. The purpose of this study is to analyze agrarian conflicts in Pakel Village with a focus on collaboration between the government, private sector, and the community in resolving land disputes between PT Bumi Sari Maju and the village community. The research method uses a library research approach. The results showed that collaboration between the government, private sector, and the community was effective in resolving agrarian conflicts in Pakel Village. Inclusive and participatory governance can benefit when the government, private sector, and community work together. Just and sustainable solutions can be achieved through mutual understanding, which increases social and economic stability in Pakel Village. Through an in-depth understanding of the agrarian conflict in Pakel Village, Banyuwangi, this research makes a significant contribution to the advancement of governance and political science. This research opens new insights into governance and agrarian conflict management by looking at the collaboration of government, private sector and community in handling the land dispute between PT Bumi Sari Maju and villagers. By involving the government, private sector, and community, a common understanding is formed that leads to a fair and sustainable resolution.Keywords:Â Agrarian Conflict, Pakel Village, and Collaborative Governance.